La memoria como ente regulador del comportamiento humano (2015)
Memory, followed by knowledge, is presented as a way to overcome the ephemeral temporality of existence, as memory is not only a faculty that stores information, it also creates and constitutes a living structure of every human being. Knowledge, in turn, is what allows awareness of the experiences of life, understanding consciousness as a way to realize something, an object, a quality, a situation or particular facts of external life. Thus, the memory updates the existence of every human being. The human’s positive or negative actions have existed in a past time, and it is in the present, where from these experiences one tries to regulate the behavior of society, so thanks to the evocation of the past, it is possible to reconstruct what has been lived. In a certain way, what is constructed is life in itself throughout the deepest memories that come back when there is an affectation caused by a particular situation in the present.